John of Holland on Epistemic Sophisms - Hanke, Miroslav (Vivarium, 2025)
The Sophismata attributed to John of Holland (fl. 1369) are preserved in three fourteenth-century manuscripts. The second part of the text contains three (bundles of) epistemic sophisms entitled “scitum a te est tibi dubium,” “tu dubitas an scis esse sicut a significat,” and “a magis est scitum quam b.” The first two develop William Heytesbury’s Regulae solvendi sophismata and De sensu composito et diviso by incorporating the theory of sentential meaning introduced in Richard Billingham’s Terminus est in quem and De sensu composito et diviso, and discuss the logic of epistemic statements and iterated modalities. The third sophism offers an interpretation of Aristotelian epistemology in terms of a mathematical framework developed by the Oxford Calculators, possibly drawing on John Dumbleton’s Summa logicae et philosophiae naturalis.